Educação para a cidadania: a experiência da comissão 'A OAB/RJ vai à Escola' - Arruda, Érica Maia C. (2007)
The objective of this study is to present and to analyze the Project 'A OAB/RJ vai à Escola' institutional social project developed by the Order of Lawyers of Brazil. The methodology of field research, with application of questionnaires and interviews, will provide one better understanding of the questionings that surround the project since its creation, with emphasis in its evaluation, especially on its validity and effectiveness as instrument for the retaken of the social function of the lawyer, of a positive group’s image and the role of OAB as institution capable to influence in Brazilian’s society life.